Advances in autonomic dysfunction research in Parkinson’s disease - Xu, Hongjia; Zheng, Xiaolei; Xing, Xinyue; Bi, Zhichao; Wang, Dewei; Zhang, Cheng; Wei, Lifei; Jin, Yulin; Xu, Shunliang (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease (PD) is a prevalent neurodegenerative disorder, best known for its motor symptoms such as resting tremor, muscle rigidity, and bradykinesia. However, autonomic dysfunction is an important non-motor aspect that often brings considerable discomfort and distress to both patients and their families. In this review, we summarize recent advances in understanding the pathophysiological mechanisms of autonomic dysfunction and explore its relationship with other clinical features. Our aim is to discover novel potential diagnostic and therapeutic strategies, alleviate patient suffering, and pave the way for future clinical and basic research.